Epidemics, public health workers, and 'heroism' in cinematic perspective. Issue 4 (20th October 2021) - Han, Qijun; Curtis, Daniel R.
Abstract : During COVID-19, acts of 'heroism' – particularly by ordinary people 'from below' – have been foregrounded, prompting complicated ethical issues in the public health context. By analysing examples from a large corpus of films about epidemics across the twentieth- and twenty-first centuries, this article investigates how cinema has represented public health workers. We find that the public health worker in epidemic-related films tends to be elite or an authority figure with expertise, often male – whose personal burden and sacrifice goes unrecognised by others, or even directly challenged 'from below'. However, although the public health worker as 'ordinary hero' rarely features, the 'human' side of epidemiologists, physicians and bacteriologists – through either personal redemption and a return to more humble roots, or recognition of personal error, questioning of official regulations and authorities, and eccentric and unorthodox behaviour – makes these 'elite' figures appear more ordinary, bridging the gap between the two.